The Use of benefit cost analysis to assess adaptation and mitigation interventions in the Caribbean : case studies - Bynoe, Mark (Caribbean Community Climate Change Centre (CCCCC) BelmopanBZ, 2014)
Sets out the practical application of cost benefit analysis to help clarify and guide decision making within highly climate vulnerable countries of the Caribbean to build resilence, both economically and socially, and to cope with the impacts of climate change.